Antibiotic Susceptibility Pattern of Bacterial Pathogens Isolated from Infected Lesions - Sherchan, Jatan Bahadur; Gurung, Pranita (Journal of Nepal Health Research Council, 2019)
Background: Wound infection with multidrug resistant bacteria along with risk factors is a major burden and challenge to the health care persons. This study focuses on antibiotic susceptibility pattern of bacterial isolates and risk factors of patients with infected wounds.Methods: This was a cross-sectional study conducted between November 2017 to June 2018 in Kathmandu University Hospital. Pus sample and wound swabs collected from patients during the study period were included. All microbiological processing were done following standard guidelines and patient’s information was collected following ethical guidelines.Results: Total number of patients observed for wound infection was 2,763. Pathogenic bacteria were detected in 252(9.12%) samples. 167(66.27%) were multidrug resistant. 118(46.82%) had risk factors. Among risk factors 14 had malignancy, 12 had diabetes, 32 were above age 60 without other risk factors, 45 received prior antibiotics and had critical illness and 15 were renal failure patients. Multidrug resistant bacteria was detected more among patients with risk factors 101(85.59%) in comparison to patients without risk factor 66(49.25%). When p value was calculated it was found significant. (p=<0.05).Conclusions: Significant amount of multidrug resistant bacteria were found in wounds of patients with risk factors. Prevention of wound infection by taking care of postoperative wounds, controlling and treating the risk factors, avoiding misuse of antibiotics and early microbiological analysis of infected wound might help to reduce the burden in healthcare centers.Keywords: Extended spectrum beta-lactamase; methicillin resistant staphylococcus aureus; multidrug resistant.